Konsep dan Arah Kebijakan Pemerintah dalam Pembangunan Pertanian di Indonesia - Rahmayandi Mulda (JURNAL TRIAS POLITIKA, 2017)
Abstract The government's policy on development in Indonesia is considered to be impartial in the agriculture sector, from observations, the portion of the budget each year is mostly channeled to other sectors, such as education, health, security and other routine expenditures such as salaries and operations, agriculture is considered very minimal, whereas more than half of the population in Indonesia works in the agricultural sector. The farmers are still complaining about infrastructure problems such as dams, irrigation, and farm roads. In addition, the quality of human resources working in the agricultural sector is still low, the price stability of production is uncertain so that at any time can harm the farmers, the survival of the survivors are allowed by the government when they have great service in encouraging development. The number of problems that occurred in the agricultural sector became the basis of this paper. This research is based on qualitative research, where researchers collect various data field and conduct a deep analysis of the data and on the problems that occur. The conclusion of this research is that government should direct development in agriculture sector so that people get welfare by making policies or regulations that favor the farmers by improving the quality of human resources in the agricultural sector, the availability of facilities and infrastructure, the guarantee of the price of agricultural products and the guarantee of survival farmers. Keywords: policy, government, development, agriculture Abstrak Kebijakan pemerintah dalam pembangunan di Indonesia dinilai belum memihak pada sektor pertanian, dari hasil pengamatan, porsi anggaran tiap tahunnya lebih banyak tersalurkan pada sektor-sektor yang lain, seperti pendidikan, kesehatan, keamanan maupun belanja rutin lainnya seperti gaji pegawai dan operasional, sedangkan untuk sektor pertanian dinilai sangat minim, padahal lebih dari setengah jumlah penduduk di Indonesia bekerja di sektor pertanian. Para petani masih banyak mengeluhkan masalah infrastruktur seperti bendungan, irigasi, maupun jalan tani, selain itu kualitas sumber daya manusia yang bekerja disektor pertanian masih rendah, stabilitas harga hasil produksi tidak menentu sehingga sewaktu-waktu dapat merugikan para petani, jaminan kelansungan hidup para petani dibiarkan begitu saja oleh pemerintah padahal mereka punya jasa besar dalam mendorong pembangunan. Banyaknya masalah yang terjadi disektor pertanian tersebut menjadi dasar dari tulisan ini. Penelitian ini didasarkan pada penelitian kualitatif, dimana peneliti mengumpulkan berbagai data dilapangan dan melakukan analisis yang mendalam terhadap data-data maupun pada persoalan-persoalan yang terjadi. Kesimpulan dari penelitian ini adalah pemerintah seharusnya mengarahkan pembangunan pada sektor pertanian sehingga masyarakat mendapatkan kesejahteraan dengan membuat kebijakan atau regulasi yang memihak kepada petani dengan cara peningkatan kualitas sumber daya manusia di sektor pertanian, ketersediaan sarana dan prasarana, jaminan harga hasil produksi pertanian dan jaminan kelangsungan hidup para petani. Kata kunci: kebijakan, pemerintah, pembagunan, pertanian